Improntas africanas : la negredumbre en la novela colombiana (2020)
This paper aims to analyze Colombian novels that configure an important tradition within the canon of literature and in which the presence of the children of the African diaspora stands out: María (1867) by Jorge Isaacs, La marquesa de Yolombó (1926) by Tomás Carrasquilla, Las estrellas son negras (1949) by Arnoldo Palacios, Changó, el gran putas (1983) by Manuel Zapata Olivella, La ceiba de la memoria (2007) by Roberto Burgos Cantor and La hoguera lame mi piel con cariño de perro (2015) by Adelaida Fernández. From a comparative perspective, the relationships between these novels will be shown to appreciate the genesis of that representation, which was brought to its maximum poetic expression by Manuel Zapata Olivella in Changó, el gran putas, a fresco ambitious historical-mythical of the African diaspora, built from an afro-centered vision, pioneer in Latin America which anticipated to the post-colonial theories.